Protective Effects of Momordica charantia (Bitter Melon) against Metho-trexate-induced Kidney Damage - ÖZBEYLİ, DİLEK (My University, 2023)
Background: Methotrexate is a cytotoxic chemotherapeutic agent that has severe side ef-fects, such as nephrotoxicity. Momordica charantia is a bright yellow-orange fruity plant that has been shown to have antioxidant, antidiabetic, and anti-inflammatory properties. Methods: 24 Sprague Dawley male rats were divided into three experimental groups (8 rats in each): Control (C); Methotrexate (MTX); and Methotrexate plus Momordica charantia (MTX+MC). All rats were fed ad libitum and tap water. Methotrexate was administered at 20 mg/kg intraperitoneally as a single dose. In the MTX+MC group, MC was administered at a dose of 50mg/kg for 5 days orally. At the end of the 5th day, the rats were decapitated and kidney samples were taken to analyze glutathione (GSH), malondialdehyde (MDA), myeloperoxidase (MPO), 8-hydroxy-2\"-deoxyguanosine (8-OHdG) and caspase-3 activity. Data was analyzed with GraphPad Prism 5.0. Results: Findings showed that while there was a significant increase in MDA, MPO, 8-OHdG levels, and an essential reduction in GSH levels in the MTX-treated group when compared with the control group, bitter melon treatment significantly reversed MDA, MPO, and 8-OHdG levels (p< 0.001). GSH level elevation was observed in the MTX-MC group when compared to the MTX-treated group (p< 0.001). Conclusion: This study showed that bitter melon is thought to have a protective effect against kidney damage caused by methotrexate. With future studies, we believe that the use of bitter melon extract as a protective agent in kidney damage caused by drug-induced oxidative damage will bring an innova-tive approach to treatment.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); kidney; methotrexate; Momordica charantia; nephrotoxicity; oxidative damage; protective effect